Praesumptio at John Paul II Code of Canon Law of 1983 - DULLAK, KAZIMIERZ (Prawo Kanoniczne, 2017)
There is variety of synonyms being used in Polish language to describe Latin praesumptio. At law sciences presumption is an interdisciplinary phrase and so it is not unambiguous. Therefore it is worth monitoring the types of the presumptions and the context of their appearance at John Paul II Code of Canon Law (CCL) of 1983. In general, we divide the presumptions into actual or judicial ones and those of law – assumed by the legislator. The former ones are drawn from authentic prerequisites. It creates the possibility to reach an objective truth. The more consistent conclusions that the judge will draw from different prerequisites the greater possibility will be reached. The latter ones – the presumptions of law – rely on assuming some facts, based on legal provisions, as proven, in case of lack of the contrary evidence. They’re divided into ordinary (relative) and absolute ones. The ordinary presumption can be refuted if false conclusions are proven. An absolute presumption takes place if the legislator refuses to admit directly the contrary evidence and assumes indirect one. The Author of the Code applies the ordinary presumptions of law only (mutable ones) which means that they can be refuted by counter-evidence. As regards the actual presumptions – they do not occur at CCL-83. They’re assumed by the judge during the trial. The John Paul II CCL applies the presumption of law with respect to the persons, circumstances and objects. Based on thorough analysis of the code contents it results that the most of the presumptions relates to the circumstances (there are as much as 13); we’ll find two less as regards the persons and only three regarding the objects. Of all 27 presumptions applied in CCL – we’ll find 14 in Book IV regulating the office of sanctifying in the Church, 7 applies to general norms (Book I) and the remaining ones we’ll find in Books: III, V, VI and VII; the last 2 contains Book II. Most of the presumptions in CCL occur in canons referring to the marriage.